Genetic diversity in fragmented populations of the critically endangered spider orchid Caladenia huegelii: Implications for conservation - Swarts, N.; Sinclair, E.; Krauss, S.; Dixon, Kingsley (Springer, 2009)
The Orchidaceae is characterised by a diverse range of life histories, reproductive strategies and geographic distribution, reflected in a variety of patterns in the population genetic structure of different species. In this study, the genetic diversity and structure was assessed within and among remnant populations of the critically endangered sexually deceptive orchid, Caladenia huegelii. This species has experienced severe recent habitat loss in a landscape marked by ancient patterns of population fragmentation within the Southwest Australian Floristic Region, a global biodiversity hotspot. Using seven polymorphic microsatellite loci, high levels of within-population diversity (mean alleles/locus = 6.73; mean HE = 0.690), weak genetic structuring among 13 remnant populations (FST = 0.047) and a consistent deficit of heterozygotes from Hardy-Weinberg expectation were found across all populations (mean FIS = 0.22). Positive inbreeding coefficients are most likely due to Wahlund effects and/or inbreeding effects from highly correlated paternity and typically low fruit set. Indirect estimates of gene flow (Nm = 5.09 using FST; Nm = 3.12 using the private alleles method) among populations reflects a historical capacity for gene flow through long distance pollen dispersal by sexually deceived wasp pollinators and/or long range dispersal of dust-like orchid seed. However, current levels of gene flow may be impacted by habitat destruction, fragmentation and reduced population size. A genetically divergent population was identified, which should be a high priority for conservation managers. Very weak genetic differentiation indicates that the movement and mixing of seeds from different populations for reintroduction programs should result in minimal negative genetic effects. © Springer Science+Business Media B.V. 2008.